Design, Synthesis, Molecular Modeling, and Anticancer Evaluation of New VEGFR-2 Inhibitors Based on the Indolin-2-One Scaffold - Mohamed A. Abdelgawad; Alaa M. Hayallah; Syed Nasir Abbas Bukhari; Arafa Musa; Mohammed Elmowafy; Hamdy M. Abdel-Rahman; Mohammed K. Abd El-Gaber (MDPI AG, 2022)
A new series of indoline-2-one derivatives was designed and synthesized based on the essential pharmacophoric features of VEGFR-2 inhibitors. Anti-proliferative activities were assessed for all derivatives against breast (MCF-7) and liver (HepG2) cancer cell lines, using sunitinib as a reference agent. The most potent anti-proliferative derivatives were evaluated for their VEGFR-2 inhibition activity. The effects of the most potent inhibitor, 17a, on cell cycle, apoptosis, and expression of apoptotic markers (caspase-3&-9, BAX, and Bcl-2) were studied. Molecular modeling studies, such as docking simulations, physicochemical properties prediction, and pharmacokinetic profiling were performed. The results revealed that derivatives 5b, 10e, 10g, 15a, and 17a exhibited potent anticancer activities with IC50 values from 0.74-4.62 µM against MCF-7 cell line (sunitinib IC50 = 4.77 µM) and from 1.13-8.81 µM against HepG2 cell line (sunitinib IC50 = 2.23 µM). Furthermore, these compounds displayed potent VEGFR-2 inhibitory activities with IC50 values of 0.160, 0.358, 0.087, 0.180, and 0.078 µM, respectively (sunitinib IC50 = 0.139 µM). Cell cycle analysis demonstrated the ability of 17a to induce a cell cycle arrest of the HepG2 cells at the S phase and increase the total apoptosis by 3.5-fold. Moreover, 17a upregulated the expression levels of apoptotic markers caspase-3 and -9 by 6.9-fold and 3.7-fold, respectively. In addition, 17a increased the expression level of BAX by 2.7-fold while decreasing the expression level of Bcl-2 by 1.9-fold. The molecular docking simulations displayed enhanced binding interactions and similar placement as sunitinib inside the active pocket of VEGFR-2. The molecular modeling calculations showed that all the test compounds were in accordance with Lipinski and Veber rules for oral bioavailability and had promising drug-likeness behavior.